Design of a Web-based Letter Making Information System for SD Negeri 2 Indonesiana, Tidore Islands City - bahta, said d; -, Rahmajati (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The use of Microsoft Word for letter creation is neither effective nor efficient, as it requires a significant amount of time to search for data from printed or digital documents, adjust letter templates, and manually re-enter data, increasing the likelihood of errors. Therefore, a system that can automatically integrate and connect data is needed to streamline the letter creation process. This research develops a Web-Based Letter Information System using the waterfall methodology, which includes stages such as analysis, design, implementation, testing, and maintenance. The final result of this study is a web-based letter information system designed to simplify the letter creation process for staff and students.